Potensi Aktivitas Antioksidan dan Antibakteri Ekstrak Etanol Daun Kari (Murraya koenigii) terhadap Propionibacterium acnes - Nasri, Nasri; Kaban, Vera Estefania; Rani, Zulmai; Suci, Nurul; Ferendina, Imelda; Tania, Chyntia Glori (Journal of Pharmaceutical and Sciences, 2025)
Indonesia is renowned for its rich natural resources, particularly medicinal plants with significant therapeutic potential. This study examined how the ethanolic extract of curry leaves (Murraya koenigii) can act as an antioxidant and antibacterial agent against Propionibacterium acnes, the primary cause of acne vulgaris. This study used phytochemical screening to identify secondary metabolites, such as alkaloids, flavonoids, tannins, saponins, and glycosides, which are associated with biological activities such as killing bacteria and protecting cells from damage. The DPPH method for testing antioxidants showed that the extract had an IC50 value of 45.88 mg/L, which is not significantly different from quercetin as a reference, at 23.7 mg/L. This result is still significant for the strong antioxidant category. We assessed antibacterial efficiency using a disc diffusion technique, which showed a zone of inhibition corresponding to the extract concentration. The widest zone of inhibition, measuring 17.77 ± 0.15 mm, was recorded at a concentration of 250 mg/mL, classifying its activity as strong by existing standards. These findings underscore the extract's promise as a natural acne therapy, addressing bacterial growth and oxidative stress. Furthermore, these results support the development of safe and efficacious pharmaceutical or cosmetic products derived from natural components. Future investigations should examine synergistic formulations and enhance bioavailability to optimize therapeutic outcomes.